Pengaruh Pelatihan Motivasi Berprestasi terhadap Peningkatan Efikasi Diri Pada Mahasiswa Kedokteran di Universitas "Z" - Shinta Putri Megawati (JIP (Jurnal Intervensi Psikologi), 2017)
This study was aimed understand the influence of Achievement Motivation Training in increase self efficacy of medicine students in Islamic University of Indonesia. Research design of this study was one-group multiplepre-test post-test design on quasi experiment with 173 subjects of experimental group in 2 days training. Data collected by self-efficacy scale from Bandura’s theory (1997). Analysis of the data used non parametrical statistic by Wilcoxon Signed-Rank Test. Results showed that Z-score was -10.058 (p < 0.000).Keywords: Achievement Motivation Training, self-efficacy